2018
DOI: 10.1039/c7cc09698d
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable increase in the rate of the catalytic epoxidation of electron deficient styrenes through the addition of Sc(OTf)3 to the MnTMTACN catalyst

Abstract: The effect of Lewis acids on the catalytic activity of [Mn(μ-O)(TMTACN)](PF) in the epoxidation of styrenes using hydrogen peroxide as the oxidant has shown that the addition of Sc(OTf) at low catalytic loading results in a very significant increase in the efficiency of the catalyst and a reduction of the reaction time to only 3 minutes in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Although the use of electron rich olefins as the substrate tended to provide higher reactivity, the tendency was hard to declare with respect to the enantioselectivity (Entries 5-8). To investigate whether the reaction proceeds via radical species or a concerted mechanism, a radical clock experiment [22] using cyclopropane compound 14 [23] and catalyst 3e was conducted ( Figure 4). This experiment revealed that the reaction proceeds via a radical mechanism if the cyclopropane-ringopened product 18 is obtained.…”
Section: Entrymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of electron rich olefins as the substrate tended to provide higher reactivity, the tendency was hard to declare with respect to the enantioselectivity (Entries 5-8). To investigate whether the reaction proceeds via radical species or a concerted mechanism, a radical clock experiment [22] using cyclopropane compound 14 [23] and catalyst 3e was conducted ( Figure 4). This experiment revealed that the reaction proceeds via a radical mechanism if the cyclopropane-ringopened product 18 is obtained.…”
Section: Entrymentioning
confidence: 99%
“…Radical clock experiment. [23] oxidizing reagent screening (Table 2), aerobic oxidation conditions afforded a dramatically lower stereoselectivity than hypervalent iodine conditions (Entry 4 vs. Entry 1).…”
Section: Entrymentioning
confidence: 99%
“…Starting from the first example regarding catalytic ability of Yb(OTf) 3 , many processes proved to be promoted by these metals in aqueous media [27]. More recently, Scandium(III) and Ytterbium(III) triflates have been used as cocatalysts of Mn complexes in the epoxidation of styrene [12]. To date, none of them have been employed in the oxidation of unsaturated fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Molybdenum and some rare earth derivatives (Sc and Yb), by their Lewis acid properties, displayed interesting activity in the oxidation of olefins [10][11][12], therefore, we planned their involvement in the oxidation of oleic acid 1 and corresponding methyl ester 1a, to replace the noneco-friendly and unrecyclable HBF 4 and H 3 PO 4 .…”
Section: Chart (1) Oxidation Waysmentioning
confidence: 99%
“…Binding of redox-inactive metal ions including Ca 2 + ion to the oxo moiety of high-valent manganese(IV)-oxo complexes is reported to result in enhancement of the redox reactivity. [8][9][10][11][12][13][14][15][16] Photoexcitation of a Mn IV -oxo complex binding two scandium ions, [(Bn-TPEN) Mn IV (O)] 2 + À (Sc(OTf) 3 ) 2 (Bn-TPEN = N-benzyl-N,N',N'-tris (2-pyridylmethyl)-1,2-diaminoethane) [12] is also reported to result in the formation of a long-lived photoexcited state with a lifetime of 6.4 μs, which exhibits high redox reactivity, capable of hydroxylating benzene with water to produce phenol. [17] Generation of such long-lived photoexcited state of a manganese(IV)-oxo complex provides an excellent photooxidant for oxidation of organic substrates.…”
Section: Introductionmentioning
confidence: 99%